Enhancing trade union leadership lesson from the past experience - Mahadirin Hj.Ahmad (Universitas Hasanuddin, 2024)
Leadership in the trade union is an important factor in determining the successful function of the union to the members. With true characteristics, leader of union can unify their members and working together to achieve their goals. Union leader also have an important role to create a good spirit within the members. All this can be achieved if the person was selected as a leader have a right attitude and willing to do a sacrifice. By defining the attitude, this paper will examine the experience of union leader who has a characteristic in pursue their goals. The true experiences are involved with two different actors. First actor is leadership in Western perspective in 1912 by focusing to Mr. Benjamin Kartz and Mr. David Kaufman. The second actor was Mr. Saito Yasuji represent the East Leadership in 1940. By focusing on qualitative method, this paper will explain what the attitudes and characteristics of leader in union are by elaborating the actors are mentioned above. Some of the finding shows all actors has a willingness to help others and strong aspirations to fight for their rights. These spirit and attitude should take as a lesson for the union leader today as an aspiration to function effectively during the union mobilisation and daily function.